Stable biochemically micro-patterned hydrogel layers control specific cell adhesion and allow long term cyclic tensile strain experiments - Greiner, Alexandra M.; Spatz, Joachim P. (Macromolecular bioscience, 2014)
Poly(dimethylsiloxane) can be covalently coated with ultrathin NCO-sP(EO-stat-PO) hydrogel layers which permit covalent binding of cell adhesive moieties, while minimizing unspecific cell adhesion on non-functionalized areas. We applied long term uniaxial cyclic tensile strain (CTS) and revealed (a) the preservation of protein and cell-repellent properties of the NCO-sP(EO-stat-PO) coating and (b) the stability and bioactivity of a covalently bound fibronectin (FN) line pattern. We studied the adhesion of human dermal fibroblast (HDFs) on non-modified NCO-sP(EO-stat-PO) coatings and on the FN. HDFs adhered to FN and oriented their cell bodies and actin fibers along the FN lines independently of the direction of CTS. This mechanical long term stability of the bioactive, patterned surface allows unraveling biomechanical stimuli for cellular signaling and behavior to understand physiological and pathological cell phenomenon. Additionally, it allows for the application in wound healing assays, tissue engineering, and implant development demanding spatial control over specific cell adhesion.
Gesehen am 29.09.2020